Cumulative effects of genetic risk variants on the development of common atherosclerosis. (March 2011) - Tsuchiya, Takafumi; Okada, Shuichi; Shimizu, Hiroyuki; Mori, Masatomo
Evaluation of: Rasmussen-Torvik LJ, Li M, Kao WH et al. Association of a fasting glucose genetic risk score with subclinical atherosclerosis: the Atherosclerosis Risk in Communities (ARIC) study. Diabetes 60(1), 331––335 (2011). Rapid advances in microarray technology have made it possible to quickly retrieve comprehensive information about a genomic region using thousands of samples. Genome-wide association studies have successfully identified a large number of genetic variants strongly related to complex phenotypes and diseases. Previous studies have suggested that the predictive value could be improved by combining multiple genetic variants. The study under evaluation in this article described a new model in the prediction of a complex phenotype using multiple genetic factors with well-replicated associations. The findings of this study may indicate a new biochemical pathway involved in the development of atherosclerosis.